#67 : Fatty Acid Supplementation into Warming Solutions Improves Outgrowth Competence Human Vitrified Blastocysts - Ayano Sawado; Kenji Ezoe; Kazuki Ohata; Tetsuya Miki; Ayumi Amagai; Kiyoe Shimazaki; Tadashi Okimura; Keiichi Kato (Fertility & Reproduction, 2023)
Background and Aims: The vitrification procedure decreased intracellular lipid content and subsequent developmental competence. Furthermore, a recent study reported that fatty acid (FA) supplementation into warming solutions increased intracellular lipid content and improved developmental competence by stimulating the beta-oxidation pathway in mice and bovines. However, in humans, the effects of FA addition to warming solutions on the viability of vitrified blastocysts remain unclear. In this study, we examined the implantation competence of blastocysts warmed by using the FA-supplemented solutions by comparing the in vitro outgrowth. Method: A total of 216 discarded human vitrified blastocysts donated for research by consenting couples were randomly allocated, to be warmed in solutions either with (FA, n = 98) or without FA (control, n = 118). Vitrified blastocysts were cultured for 120 min after warming. The blastocysts were plated on fibronectin-coated dishes and cultured for 96 h to assess the blastocyst competency for adhesion and outgrowth. Results: The embryo characteristics were comparable between the control and FA groups. The adhesion rate at 96 h after the outgrowth culture in the FA group (74.5%) was comparable with that in the control group (74.6%). The 1.3-fold increase in the outgrowth area was observed in the FA group, compared to the control group ([Formula: see text] = 0.0371). Furthermore, the sub-group analysis demonstrated that a more beneficial effect of FA supplementation on blastocyst outgrowth was observed when the trophectoderm was evaluated as grade A ([Formula: see text] = 0.0065). Conclusion: The FA supplementation into warming solutions increased the outgrowth competence of vitrified human blastocysts. These results suggest that the pregnancy outcomes, including the implantation rate, after frozen blastocyst transfers would be improved by using the FA-supplemented solutions.